2022
DOI: 10.3390/ijms232315397
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles of Urinary Extracellular Vesicles Released during the Inactive and Active Phases of Aged Male Mice with Spontaneous Hypertension

Abstract: Hypertension remains a major problem, especially in the elderly, as it increases the risk for cardiovascular, coronary artery, cerebrovascular, and kidney diseases. Extracellular vesicles (EVs) play a role in the aging process and contribute to pathophysiology. Our goal was to examine differences in lipid profiles of urinary EVs (uEVs) collected during the inactive and active phases of aged mice and investigate whether these EVs regulate the density of lipid rafts in mouse cortical collecting duct (mpkCCD) pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Recent work highlighted the role of the circadian rhythm in EV production and function. In humans and rodents, the concentration of circulating EVs increases during the active phase and decreases over inactive phase [101][102][103][104]. In mice, this was found to be inversely related to corticosterone levels [102].…”
Section: Evs Are Affected By Homeostasismentioning
confidence: 99%
“…Recent work highlighted the role of the circadian rhythm in EV production and function. In humans and rodents, the concentration of circulating EVs increases during the active phase and decreases over inactive phase [101][102][103][104]. In mice, this was found to be inversely related to corticosterone levels [102].…”
Section: Evs Are Affected By Homeostasismentioning
confidence: 99%
“…Lipidomic profiling of EVs offers a comprehensive view of the lipid composition, reflective of cellular conditions in the cardiovascular environment. These lipid signatures, including bioactive lipid mediators, shed light on lipid metabolism dysregulation, a hallmark of hypertension [34,35]. Furthermore, characterizing the surface proteome of EVs allows the identification of disease-specific markers of malaria and hyperlipoidemia, facilitating the development of highly selective diagnostic tools [23,36].…”
Section: Extracellular Vesicle Molecular Signaturesmentioning
confidence: 99%
“…A study by Lugo et al showed differences in the amount of annexin A2, GAPDH, TSG101, and caveolin-1 proteins, as well as lipids including specific hexosylceramides, monoacylglycerols, phosphatidylcholines, lysophosphatidylethanolamine, phosphatidylethanolamine, and phosphatidylglycerol enriched in uEVs from male and female diabetic db/db mice treated with human AAT (hAAT) or the vehicle [ 42 ]. A study by Lopez et al showed differences in the amounts of syntein and flotillin proteins, as well as lipids including specific phosphatidylethanolamines, triacylglycerols, and phosphatidylcholines enriched in uEVs from aged male mice with spontaneous hypertension [ 15 ]. Yeung et al performed a functional enrichment analysis of circadian proteins and showed actin-binding and intermediate filament proteins associated with the cytoskeleton had peak abundances in small EVs that were temporally separated at 8 h and ~23 h after synchronization [ 76 ].…”
Section: Circadian Regulation Of Ev Cargo Relevant To Diabetes Researchmentioning
confidence: 99%
“…In addition, EVs are used in multiple applications [ 12 , 13 , 14 ]. EVs isolated from biological fluids including urine [ 15 ], plasma [ 16 ], and cerebrospinal fluid [ 17 ] represent a rich source of biomarkers. Additionally, the profiling of the EV cargo can be used as markers of diagnosis and prognosis [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%